2013
DOI: 10.1016/j.acalib.2012.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Reference Reviewed and Re-Envisioned: Revamping Librarian and Desk-Centric Services with LibStARs and LibAnswers

Abstract: The first section of this article reviews the literature on the changing face of reference, beginning with a discussion of the national decline in reference transactions, its causes, and the likelihood that online reference services might one day halt or reverse the decline. It then analyzes definitions of the term "reference," pointing to a disconnect between those definitions and much of the work that actually takes place at reference desks. Next, critiques of desk-centric models of reference are examined, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 17 publications
2
60
0
Order By: Relevance
“…The increased emphasis on online reference service has resulted in a de-emphasis of the physical reference desk. Freides (1983) and Stevens (2013) suggest that reference desks dissuade patrons from asking robust questions and can unwittingly cultivate the notion that the library does not provide substantive reference assistance. Freides (1983) and Stevens (2013) also note that the time and talent of professional reference librarians are often wasted on transactions that are routine or trivial in nature.…”
Section: Reference Service Trends In Academic Librariesmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased emphasis on online reference service has resulted in a de-emphasis of the physical reference desk. Freides (1983) and Stevens (2013) suggest that reference desks dissuade patrons from asking robust questions and can unwittingly cultivate the notion that the library does not provide substantive reference assistance. Freides (1983) and Stevens (2013) also note that the time and talent of professional reference librarians are often wasted on transactions that are routine or trivial in nature.…”
Section: Reference Service Trends In Academic Librariesmentioning
confidence: 99%
“…Freides (1983) and Stevens (2013) suggest that reference desks dissuade patrons from asking robust questions and can unwittingly cultivate the notion that the library does not provide substantive reference assistance. Freides (1983) and Stevens (2013) also note that the time and talent of professional reference librarians are often wasted on transactions that are routine or trivial in nature. Others have recognized the need for liaison librarians to spend more time on individual consultations and the creation of instructional materials that anticipate reference needs, rather than passively waiting for students to approach them at the reference desk (Jaguszewski & Williams, 2013).…”
Section: Reference Service Trends In Academic Librariesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Scott Carlson went as far to predict that by 2012, reference desks will no longer exist in academic libraries (2007). As the demand for reference desks declined, Christy Stevens (2013) has pointed out that online reference questions, and platforms to answer these reference questions, has been on the rise since 2005.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Still the decline in numbers A month-long discussion ensued involving the entire Library Department. Several librarians noted that the library literature indicated that the decline in reference questions was ubiquitous in academic libraries (Stevens, 2013) and that recent ethnographic studies had shown students' reluctance to ask librarians for help (Green, 2012) (Miller & Murillo, 2012). These studies, plus librarians' own observations, showed that students frequently needed the help of a skilled librarian even when they did not ask.…”
Section: Problemmentioning
confidence: 99%